Octanorm [cutaquig®], a new immunoglobulin (human) subcutaneous 16.5% solution for injection (165 mg/mL) – Biochemical characterization, pathogen safety, and stability. (July 2019) - Gelbmann, Nicola; Zöchling, Alfred; Pichotta, Alexander; Schmidt, Torben; Murányi, Andrej; Ernegger, Thomas; Pock, Katharina; Römisch, Jürgen
Abstract: Octanorm (marketed as cutaquig® in Canada and US [2018] and registered in several European countries [2019]) is a new immunoglobulin subcutaneous 16.5% liquid for the treatment of patients with primary immune deficiency (PID) and secondary immune deficiency (SID) depending on country's specific indications. Octanorm contains ≥96% human IgG and is characterized by especially low concentrations of polymers and aggregates, IgA and IgM, a physiological osmolality along with a low isoagglutinin titer. The Octanorm manufacturing process is based on the well-established IVIG octagam® 5% and 10% process, but yields a higher immunoglobulin concentration of 16.5% in the final product. Octanorm shows a distribution of immunoglobulin G subclasses closely proportional to native human plasma and comprises a broad spectrum of antibodies against infectious agents. Potential procoagulant activity is not detectable. IgG functionality and physico-chemical integrity have been demonstrated by state-of-the-art-methods. The virus safety of Octanorm is ensured via a combination of three validated independent methods as part of the manufacturing process. Substantial prion depletion during the manufacturing process has also been demonstrated. Compared with other commercially available subcutaneous immunoglobulin (SCIG) 20% products, Octanorm 16.5% shows a lower viscosity, which is a valuable feature that allows for a more comfortable infusion experience.